The Effects of Barter Trade Suspension in Sabah - Sarma Aralas; Mohd Alliff Anwar Abu Bakar; Chan, Jennifer Kim Lian (Universiti Malaysia Sabah, 2017)
The recent suspension of barter trade in Sabah, Malaysia, has caused losses in business revenues amounting to millions of ringgit and the loss of employment of hundreds of workers in the industry. We conducted a survey to quantify the impact of the barter trade suspension in major barter trade locations which included Tawau, Sandakan, and Lahad Datu, major cities in Sabah that are considered the hubs of barter trading in the state. Our survey findings show that the losses of direct income to traders due to the suspension range between RM1,680,000 - RM3,750,000 for eight traders in the survey sample conducted in May 2016. Other effects include the laying-off of barter-trade workers, and unemployment of employers, losses in the benefit of import-export activities through anticipated rising prices, losses in the diversity of consumption of imported products, and displacement of workers through relocation to other industry sectors or geographical regions to pursue new employment opportunities.